The Trend of Targeted Therapies in Chinese Patients With Ankylosing Spondylitis: Results From a Real-Life Survey - Wen, Yiquan; Hu, Zhuoran; Xie, Baozhao; Yuan, Fei; Xie, Zhengquan; Jiang, Yutong; Lin, He; Qi, Jun; Chen, Qiyun (Frontiers in Pharmacology, 2021)
Introduction Targeted medication, including mostly biologics and small-molecule chemical drugs were important therapies in ankylosing spondylitis (AS). There is still limited data on the preference of different targeted drugs in Chinese AS patients. Methods A questionnaire-based cross-sectional study was performed on AS patients from six hospitals in three provinces in South China. Anti-rheumatic diseases medication history includes the recent and previous usage of biologics or JAKi in the last complete course of treatment, disease severity, and reasons for targeted-treatment change or preference were collected. Results 354 of 366 participants responded to the online survey. Participants’ median age was 32, with a median of 7.3 years of disease duration; 79.7% were male. 63.6% of them were in the course of biologics or JAKi. Generic ETN is the most used and willing-to-use biologics though the proportion shrunk in the present compared with the previous. The choice of original-branded ADA demonstrated an increase. The preference of Secukinumab and tofacitinib depicted a quick ascending trend. Conclusion TNFi is still the most popular targeted medication for AS in China. Price influences patients’ preferences mostly. The doctor’s recommendation is also part of the equation. Rheumatologists should pay more attention to patient education to formulate targeted therapeutic plans.